Effect of Gamma Radiation on Morpho-Physiological Characters of Soybean (Journal of Environmental Science and Natural Resources, 2015)
An experiment was carried out at the experimental farm of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during the period from January, 2011 to April, 2011. The study was conducted to evaluate the effect of gamma radiation on morpho-physiological characters of BARI soybean. Four levels of gamma irradiation viz. 200, 300, 400 and 500 Gy ?-ray from 60C source and control were irradiated on assigned two genotypes viz. BARI soybean 5 and BARI soybean 6. Data for growth analyses were collected at different days after sowing. Results revealed that the soybean varieties and gamma irradiation significantly affected morpho-physiological characters where BARI soybean 5 and 200 Gy ?-ray levels produced the greater results alone or combinations. This combination produced the tallest plant (37.42 cm), maximum leaf and branch plant-1 (23.15 and 2.10) at 75 DAS. 200 Gy ?-ray irradiated plants of BARI soybean 5 produced the highest seed yield (2373.70 kg ha-1) followed by control treatment (1887.90 kg ha-1) at the same variety. On the other hand, the plants consequential from 500 Gy ?-ray radiated of BARI soybean 5 had shown the lowest seed yield (1050.70 kg ha-1). This result indicating that irradiation significantly decreased on seed yield with increasing doses of gamma rays. So, the variety BARI soybean 5 and 200 Gy ?-ray alone or combination had outstanding superiority for plant growth over the other gamma ray levels.DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22199 J. Environ. Sci. & Natural Resources, 7(2): 25-30 2014